New roles of SHOX as regulator of target genes - Rappold, Gudrun; Durand, Claudia; Decker, Eva; Marchini, Antonio; Schneider, Katja U. (Pediatric endocrinology reviews, 2012)
The homeobox gene SHOX encodes a transcription factor which is important for normal limb development. Approximately 5 to 10% of short patients exhibit a mutation or deletion in either the SHOX gene or its downstream enhancer regions. In humans, SHOX deficiency has been associated with various short stature syndromes as well as non-syndromic idiopathic short stature. A common feature of these syndromes is disproportionate short stature with a particular shortening of the forearms and lower legs. Madelung deformity, cubitus valgus, high-arched palate and muscular hypertrophy also differed markedly between patients with or without SHOX gene defects. A clinical trial in patients with SHOX deficiency and Turner syndrome demonstrated highly significant growth hormone-stimulated increases in height velocity and height SDS in both groups. Employing microarray analyses and cell culture experiments, a strong effect of SHOX on the expression of the natriuretic peptide BNP and the fibroblast growth factor receptor gene FGFR3 could be demonstrated. We found that BNP was positively regulated, while Fgfr3 was negatively regulated by SHOX. A regulation that occurs mainly in the mesomelic segments, a region where SHOX is known to be strongly expressed, offers a possible explanation for the phenotypes seen in patients with FGFR3 (e.g. achondroplasia) and SHOX defects (e.g. Léri-Weill dyschondrosteosis).
Gesehen am 31.07.2018
Keine DOI vorhanden